Maximal Independent Sets in Caterpillar Graphs - Villanueva-Ilufi, M (2012)
A caterpillar graph is a tree in which the removal of all pendant vertices results in a chordless path. In this work, we determine the number of maximal independent sets (mis) in caterpillar graphs. For a general graph, this problem is Pcomplete. We provide a polynomial time algorithm to generate the whole family of mis in a caterpillar graph. We also characterize the independent graph (intersection graph of mis) and the clique graph (intersection graph of cliques) of complete caterpillar graphs. © 2011 Elsevier B.V. All rights reserved.